Cultural Resilience in the Face of Crisis A Case Study of the COVID-19 Pandemic - Singh, Kapoor; Deepak, Anil; Asha, Pria (Journal Social Humanity Perspective, 2023)
The COVID-19 pandemic has had a significant impact on human cultures all across the world, presenting people with the challenge of responding to and adapting to unheard-of disasters. Cultural expressions have become crucial channels for people and communities to cope, connect, and find resilience during this time. This paper examines the subject of "Cultural Resilience in the Face of Crisis" with a particular emphasis on the COVID-19 pandemic as a case study. Understanding how culture responds to and adjusts to global crises is the fundamental goal, with a focus on cultural expressions in the areas of art, literature, media, and identity. The study uses a qualitative methodology that includes surveys to determine public attitudes, in-depth interviews with artists and cultural practitioners, and content analysis of cultural items. The study uncovers the various ways that culture expresses resilience, solidarity, and optimism during trying times through the investigation of artworks, literary works, media depictions, and cultural practices. It explores how cultural identity affects both individual and group reactions, emphasizing the importance of cultural unity in promoting resilience. Findings emphasize the value of cultural expressions in the arts, literature, and media as vital tools for crisis communication, recovery, and adaptation. The study emphasizes the significance of moral media images as well as the necessity of addressing prejudice and overlapping inequities. The study also highlights the importance of cultural policy and support in safeguarding cultural assets and aiding artists in difficult times.